Incongruent plastid and nuclear DNA phylogenies reveal ancient intergeneric hybridization in Pilosella hawkweeds (Hieracium, Cichorieae, Asteraceae) - Fehrer, Judith; Gemeinholzer, Birgit; Chrtek, Jindrich; Bräutigam, Siegfried (Molecular phylogenetics and evolution, 2007)
Phylogenetic relationships for Hieracium subgen. Pilosella were inferred from chloroplast (trnT-trnL, matK) and nuclear (ITS) sequence data. Chloroplast markers revealed the existence of two divergent haplotype groups within the subgenus that did not correspond to presumed relationships. Furthermore, chloroplast haplotypes of the genera Hispidella and Andryala nested each within one of these groups. In contrast, ITS data were generally in accord with morphology and other evidence and were therefore assumed to reflect the true phylogeny. They revealed a sister relationship between Pilosella and Hispidella and a joint clade of Hieracium subgenera Hieracium and Chionoracium (Stenotheca) while genus Andryala represented a third major lineage of the final ingroup cluster. Detailed analysis of trnT-trnL character state evolution along the ITS tree suggested two intergeneric hybridization events between ancestral lineages that resulted in cytoplasmic transfer (from Hieracium/Chionoracium to Pilosella, and from the introgressed Pilosella lineage to Andryala). These chloroplast capture events, the first of which involved a now extinct haplotype, are the most likely explanation for the observed incongruencies between plastid and nuclear DNA markers.
Keywords: nukleotidyltransferasy; hybridizace genetická; plastidy; DNA, Intergenic; Nucleotidyltransferases; molekulární sekvence - údaje; Plastids; RNA, Transfer; Molecular Sequence Data; Endoribonucleases; RNA transferová; intergenová DNA; Sequence Analysis, DNA; buněčné jádro; Cell Nucleus; Evolution, Molecular; DNA chloroplastová; fylogeneze; sekvenční analýza DNA; endoribonukleasy; DNA, Chloroplast; Asteraceae; Hybridization, Genetic; Phylogeny; molekulární evoluce